2017
DOI: 10.1111/1756-185x.13048
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 25‐hydroxyvitamin D and vitamin D‐binding protein on bone mineral density and disease activity in Malaysian patients with rheumatoid arthritis

Abstract: In Malaysian RA patients, menopausal status and BMI were more important influences on BMD than 25(OH)D or RA disease activity. The utility of measuring VDBP levels in this population remains uncertain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 48 publications
3
10
0
Order By: Relevance
“…We compared ethnicity distribution in relation to vitamin D deficiency in RA patients and found that the concentrations of serum 25(OH)D among Malays and Indians were significantly lower compared to the Chinese. This result is consistent with the findings in our healthy controls and few other studies done in the Malaysian population as well as in the neighboring country, Singapore . The higher melanin content inhibiting the skin synthesis of vitamin D is the likely reason for the more prevalent vitamin D deficiency in Malays and Indians who have darker skin compared to the Chinese.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We compared ethnicity distribution in relation to vitamin D deficiency in RA patients and found that the concentrations of serum 25(OH)D among Malays and Indians were significantly lower compared to the Chinese. This result is consistent with the findings in our healthy controls and few other studies done in the Malaysian population as well as in the neighboring country, Singapore . The higher melanin content inhibiting the skin synthesis of vitamin D is the likely reason for the more prevalent vitamin D deficiency in Malays and Indians who have darker skin compared to the Chinese.…”
Section: Discussionsupporting
confidence: 93%
“…In contrast to our hypothesis, we observed no association between vitamin D deficiency and disease activity in RA subjects. These findings were similar to the previous Malaysian study as well as to the Japanese and Thai studies . Similar findings were also observed in Western populations .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…24 In a more recent study of female rheumatoid arthritis patients, Chinese patients had lower FN and total hip BMDs compared to Malay and Indian patients, with no difference in LS BMD. 25 Thus it would seem that in multi-ethnic populations in SEA, the Chinese will have a lower hip BMD compared to Malays and Indians with no difference in LS BMD, suggesting the need for ethnicity-based normative data for BMD.…”
Section: Bmd Differences Within Individual Se Asian Countriesmentioning
confidence: 99%
“…Another interesting issue is whether vitamin D has an inverse relation with RA activity. The evidence from various studies concerning the link between serum vitamin D concentration and disease activity is inconsistent [5][6][7]. Some studies also revealed that the impact of inadequate vitamin D levels on disease activity in the RA individuals was associated with more subjective variables (eg, Visual Analog Scale (VAS) pain, tender joint count (TJC)) than a real objective immunomodulatory effect [8].…”
Section: Introductionmentioning
confidence: 99%